Salsa Crossings : Dancing Latinidad in Los Angeles - Garcia, Cindy, 1968- (Book collections on Project MUSE., 2013)
In Los Angeles, night after night, the city's salsa clubs become social arenas where hierarchies of gender, race, and class, and of nationality, citizenship, and belonging are enacted on and off the dance floor. In an ethnography filled with dramatic narratives, Cindy García describes how local salseras/os gain social status by performing an exoticized L.A.-style salsa that distances them from club practices associated with Mexicanness. Many Latinos in Los Angeles try to avoid ""dancing like a Mexican, "" attempting to rid their dancing of techniques that might suggest that they are migran